PERANCANGAN DAN IMPLEMENTASI ROBOT PEMBANTU PENGAWAS RUANGAN - Utama, Hadian Satria; Mardjoko, Pono Budi; Wijaya, Suwandy (TESLA Jurnal Teknik Elektro UNTAR, 2006)
The designed robot will be used for surveillance purposes one of these purposes is to do monitoring in the industry line. The robot is equipped with wireless TV camera and line sensor. The robot moves in 2 ways, automatically by following the black line on the floor or by being controlled using remote control.